Synthesis of large-area 2D WS2 films and fabrication of a heterostructure for self-powered ultraviolet photodetection and imaging applications. Issue 39 (25th September 2019) - Zhao, Zhihui; Wu, Di; Guo, Jiawen; Wu, Enping; Jia, Cheng; Shi, Zhifeng; Tian, Yongtao; Li, Xinjian; Tian, Yongzhi
Abstract : High-performance self-powered ultraviolet (UV) photodetector based on a WS2 /GaN heterojunction was demonstrated, which exhibits excellent UV photoresponse properties. Significantly, this photodetector has exhibited excellent UV imaging capability. Abstract : High-performance ultraviolet (UV) photodetectors have been attracting extensive attention, due to their great importance in both military and civil applications. In recent years, the rapid development of two-dimensional (2D) materials with unique and excellent optoelectrical properties has provided an ideal platform for developing high-performance photodetectors. In this work, large-area 2D WS2 films were synthesized and a WS2 /GaN heterojunction was constructed. The as-fabricated WS2 /GaN heterojunction device has demonstrated high-sensitivity and self-powered photoresponse properties to UV signals with a large photoresponsivity of 226 mA W −1, and an ultrahigh large specific detectivity of 4 × 10 14 Jones, as well as fast response speeds at zero bias. Furthermore, a high-resolution UV imaging result with high contrast is achieved by using the as-fabricated photodetector as a sensing pixel. The results demonstrated in this work suggest that WS2 /GaN heterojunction devices have great potential in high-performance UV detection and imaging applications.